Molecular DOM composition (relative peak intensities) derived from ultra-high resolution mass spectrometry (FT-ICR-MS) - Seidel, Michael; Knoke, Melina; Klaproth, Katrin; Friebe, Matthias; Ulber, Ina Ida; Lehners, Carola; Schnetger, Bernhard; Zielinski, Oliver; Dittmar, Thorsten (In: Seidel, M et al. (2025): Biogeochemistry of dissolved organic matter in a mangrove-fringed estuary in Amazonia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974693, 2025)
We studied dissolved organic matter (DOM) dynamics in a mangrove-fringed estuary in North Brazil, linking DOM composition to redox conditions at its formation sites. By combining molecular analyses with nutrient and trace metal data, we highlight the outwelling of recalcitrant DOM as a significant contributor to coastal carbon storage and present a novel molecular index (ISuP) for distinguishing DOM sources in complex coastal ecosystems. This dataset contains dissolved organic matter (DOM) molecular data from ultrahigh-resolution mass spectrometry (Fourier-transform ion cyclotron resonance mass spectrometer, FT-ICR-MS), molecular indices calculated from the FT-ICR-MS data (ISuP and ITerr) and environmental data, including dissolved organic carbon (DOC), nutrient (NOx and phosphate), and trace metal (Fe,Mn, Ba) data. Water samples were collected along a mangrove-fringed estuary near Bragança in Pará State (Brazil). Furthermore, it contains porewater samples from eight locations in the mangrove forest and tidal water samples from a mangrove creek, as described in Knoke et al. (2024).
Keywords: DOM; FDOM; FT-ICR-MS; mangroves; nutrients; trace metals Fe/Mn/Ba